2021
DOI: 10.1302/2633-1462.22.bjo-2020-0200.r1
|View full text |Cite
|
Sign up to set email alerts
|

How to prioritize patients and redesign care to safely resume planned surgery during the COVID-19 pandemic

Abstract: Aims Restarting planned surgery during the COVID-19 pandemic is a clinical and societal priority, but it is unknown whether it can be done safely and include high-risk or complex cases. We developed a Surgical Prioritization and Allocation Guide (SPAG). Here, we validate its effectiveness and safety in COVID-free sites. Methods A multidisciplinary surgical prioritization committee developed the SPAG, incorporating procedural urgency, shared decision-making, patient safety, and biopsychosocial factors; and appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Therefore, the OKS seems to be more inclusive than exclusive when identifying those who may benefit from a TKA. Not all patients on a waiting list for a TKA are, however, equal and prioritizing according to pain severity and effects on socioeconomic consequences is difficult [ 8 , 10 , 28 ]. Rationing of TKA is inevitable when there are limited resources and demand exceeds capacity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the OKS seems to be more inclusive than exclusive when identifying those who may benefit from a TKA. Not all patients on a waiting list for a TKA are, however, equal and prioritizing according to pain severity and effects on socioeconomic consequences is difficult [ 8 , 10 , 28 ]. Rationing of TKA is inevitable when there are limited resources and demand exceeds capacity [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, priority two surgery (within a month) applies to arthroplasty patients where delays may prejudice their outcome; priority three (less than three months) applies to avascular necrosis of the hip: and priority four (more than three months) applies to uncomplicated arthroplasty [ 9 ]. All patients listed for knee arthroplasty are not equal and priority four will not be applicable to all patients [ 10 ]. Objective prioritization of patients is difficult, and authors have suggested prioritizing according to scores, applied ethics, and knee-specific function [ 8 , 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 , 18 These guidelines were shown to be effective in minimizing COVID-19 exposure to operative patients. 19 Studies have also sought to identify strategies to safely reinstate orthopaedic procedures, such as stratifying elective patients at higher risk for COVID-19-related illness by assessing comorbidities and minimizing length of hospital stay. 20 Surrogates for elective surgery, such as the use of THA for hip fractures, also showcased the ability to provide arthroplasty services safely amid the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these results are only in part comparable. However, the general picture of highly variable perception of pandemic effects on personal decision making by patients was similarly found in other entities, such as elective surgery, and in various countries, such as the UK [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 97%